SORPTION AND DESORPTION OF SELECTED ORGANIC AND INORGANIC POLLUTANTS IN SOILS COLLECTED FROM DIFFERENT AGRO-ECOLOGICAL ZONES OF NIGERIA (2015)
Environmental pollution caused by persistent and bioaccumulative toxic chemicals is a global issue in view of its effects on biota. Researches abound on the sources and concentration of soil pollutants but there is paucity of information on their sorption/desorption in Nigerian soils. This is necessary for accurate prediction of toxicity and effective remediation strategy. Therefore, this study was aimed at assessing the sorption/desorption of selected organic and inorganic pollutants in soils from different Agro-Ecological Zones (AEZs) of Nigeria. Representative composite soil samples (0-30 cm depth) were collected from the eight AEZs (15 each) and their physicochemical characteristics determined using standard methods. Soil treatments were carried out by removing Organic Matter (OM) and iron oxides to give Organic-Matter-Removed (OMR) and Iron-Oxides-Removed (IOR) samples, respectively. Batch sorptions/desorptions of pyrene and fluorene [Polycyclic Aromatic Hydrocarbons (PAHs)], Pentachlorophenol [PCP; Pesticide], and Pb(II), Cu(II), and Cd(II) [Heavy Metals (HM)] were investigated at varying times (0-4320 min.), solution pH (3-9), sorbate concentrations (20-100 μg/L PAHs; 10-40 mg/L PCP; 50-300 mg/L HM), and temperatures (25 and 40 C) for untreated, OMR and IOR soil samples. Competitive sorptions/desorptions were investigated using batch method. Data were fitted to four kinetics models [Pseudo-First-Order (PFO), Pseudo-Second-Order (PSO), Elovich, and Intra-Particle-Diffusion (IPD)] and three adsorption isotherm models [Langmuir, Freundlich, and Distributed Reactivity Model (DRM)]. Thermodynamic parameters (Gibb’s free energy-G, entropy-S, and enthalpy-H) were determined and the regression analyses were carried out. Soil pH values ranged from 6.2 to 7.4, while their Cation Exchange Capacity (CEC) ranged from 2.4 to 8.3 meq/100g. The OMR soils exhibited acidic pH (4.1-6.1) and reduced CEC (2.1-3.9 meq/100g), while IOR soils were alkaline (pH of 7.8-8.1) with increased CEC (17.9-37.9 meq/100g). Equilibrium sorptions were attained within 1440 minutes for all sorbates. Increasing pH decreased organics sorption (16.0-42.0%) but increased metals sorption (≥75.0%). Competition decreased the sorptions of organic pollutants while higher temperature increased sorptions. Metal distribution coefficients iii (Kd) values were directly proportional to OM content, and single and competitive sorptions followed the same trend: Pb(II)>Cu(II)>Cd(II). Desorptions hystereses were related to OM content: the higher the OM, the higher the hysteresis. Sorptions data fitted PSO (R2=0.99-1.00), Elovich (R2=0.90-1.00) and IPD (R2=0.71-0.96) models which suggested some degree of boundary-layer-control. Sorptions data were better described by DRM and Freundlich adsorption isotherms for PAHs and PCP, respectively; while both Langmuir and Freundlich isotherms described the metals confirming the heterogeneous nature of the soils. Sorptions of selected pollutants were spontaneous and feasible (G <–15.5kJmol-1), accompanied by low S values (1.3 kJmol-1K-1). The H values (<45.0 kJmol-1) were in the energy range associated with weak forces of interactions such as Van-der Waals, electrostatic, and π-π interactions. The sorptions of selected organic and inorganic pollutants were partly surface adsorption and partly partitioning between phases in soils. Organic matter, iron oxides and temperature were major factors controlling sorptions/desorptions. Low levels of organic matter, iron oxides and high temperature may negatively impact biota and aquifer.